Interaction between electrode materials Sr2FeCo0.5Mo0.5O6−δ and hydrogen sulfide in symmetrical solid oxide fuel cells. (24th August 2017) - Song, Yang; Zhong, Qin; Wang, Dongyu; Xu, Yalin; Tan, Wenyi
Abstract: Symmetrical Solid Oxide Fuel Cells (SSFCs) are highly competitive options for a sustainable energy future, however, its application is hindered by the development of more surfer tolerance and highly efficient electrodes. Sr2 FeCo0.5 Mo0.5 O6− δ (SFCM) was investigated as potential electrode materials for SSFCs using H2 S as a fuel directly. SFCM powders, before and after exposure to 0.05% H2 S/N2, were carried out to analyze the structure and morphology by X-ray diffraction (XRD), transmission electron microscope (TEM) and scanning electron microscope (SEM). A maximum power density of 45.69 mW cm −2 was obtained in the configuration of SSFC (SFCM/LSGM/SFCM) in 0.05% H2 S/N2 at 800 °C. SFCM had high catalytic activity in converting H2 S into SO2 without obviously deactivation. After cell test, X-ray photoelectron spectroscopy (XPS) was used to reveal the distribution of valence state of sulfur. There founding demonstrated that the SSCM has a certain surfer tolerance ability, and that understanding how the electrodes works and impact the cell performance is critical to the design of highly stable double perovskite electrodes. Highlights: The products of H2 S electrochemical oxidation over SFCM were detected. The way anode SFCM interact with fuel gas containing H2 S be explained. The maximum power density could reach 45.69 mW cm −2 in 0.05% H2 S/N2 at 800 °C. The conversion efficiency of the H2 S oxidation in the SFCM catalytic will increase to 96%.